Numerical analysis of frequency optimization and effect of liquid sodium for ultrasonic high frequency guided wave inspection of core support structure of fast breeder reactor. (May 2018) - Dhayalan, R.; Kumar, Anish; Rao, B. Purnachandra
Highlights: Ultrasonic HFGW methodology is developed for in-service inspection of MV-CSS in FBR. The transducer frequency is optimized by experimental measurement and FE simulation. The smoothed pseudo Wigner-Ville distribution (t-f) is used for analysing HFGW. The characteristics of HFGW under the influence of fluid loading is analysed by FEM. The MV-CSS with fluid boundary reduces the amplitude of HFGW by about 10 dB. Abstract: The paper discusses the numerical modeling of ultrasonic high frequency guided waves (HFGW) for nondestructive inspection of main vessel core support structure (MV-CSS) in sodium cooled prototype fast breeder reactor (PFBR). A series of 2D plain strain finite element (FE) models have been created by using an explicit scheme to optimize the transducer frequency for efficient generation of HFGW in MV-CSS. The time-frequency smoothed pseudo Wigner-Ville distribution (SPWVD) has been used to analyze the generated HFGW modes. With optimum transducer frequency, several FE models have been created with a reference defect down to 20% of 30 mm wall thickness (6 mm) on MV-CSS for analyzing the propagation behavior of HFGW under the influence of fluid loading (liquid sodium) boundary conditions at high temperature. The simulation results are validated by experimental measurements performed on a mock-up structure of the MV-CSS for frequencies in the range of 0.5–5 MHz. The amplitude response of HFGW is found to be maximum at 2.25 MHz and considerably non-dispersive. The model predictions are found to capture all features observed in the experiments. Most of the out of plane components of HFGW are leaked through the liquid sodium which in turn, affects the propagation characteristics of the guided waves in the MV-CSS. From the simulation results, it has been observed that the reference defect signal amplitude decreases with increasing temperature of liquid sodium.